Folk Museum Spanish Town, Jamaica ([Place of publication not identified] : [Publisher not identified])
Postcard depicting an original sugar mill made entirely of Jamaican hardwoods. At the left a reconstruction of a sugar boiling house.
Colour photography by Colorcraft Studios.
Keywords: Sugar factories -- Jamaica; Museums -- Jamaica; Postcards -- Jamaica